Using social cognitive theory to develop a food, nutrition, and kitchen life skills curriculum for a women's alternative incarceration program - Anderson, Kallen (My University, 2017)
Women in the criminal justice system have increased in numbers by 700% in the last 4 decades. This is 50% more of an increase compared to men who are incarcerated. Over 75% of women in the criminal justice system will return to their families as the dependent primary caretaker of their children after incarceration. To assist with this dramatic increase of incarcerated women, alternative incarceration programs have been increasing across the United States. The city of La Crosse, Wisconsin has one of these alternative incarceration programs through a partnership with the YWCA and the county's Justice Support Services called Ophelia's House. Alternative incarceration programs assist these women transition back to civilian life by connecting them with community and other services including housing, mental health treatment and counseling, physician doctor care, and more, However, there has been little education or focus on health education, specifically food and nutrition education which is necessary for the women to care for themselves and their families. Using social cognitive theory and Bloom's Taxonomy of Learning, a curriculum packet including lessons, worksheets, and a cookbook was developed for Ophelia's House. Ophelia's House staff will implement the lessons as a part of their programming.
Keywords: Health promotion; Health education